2008
DOI: 10.1002/jso.21220
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic characteristics and outcomes of gastric cancers with the MSI‐H phenotype

Abstract: Gastric cancers with MSI-H have specific clinicopathologic characteristics, such as older age at diagnosis, distal tumor location, increased tumor size, and intestinal histologic type. However, immunohistochemical staining for hMLH1 and hMSH2 is not as accurate as the PCR-based MSI test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
87
1
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(113 citation statements)
references
References 26 publications
19
87
1
2
Order By: Relevance
“…Several reports, together with our results, have demonstrated that microsatellite-unstable gastric carcinomas are significantly associated with the elderly [2,[4][5][6], women [3,5], and antral location [2,4,5,9]. These characteristics are similar to those of medullary-type, poorly differentiated adenocarcinoma of the colorectum, which is a representative MSI-positive carcinoma showing predominant occurrence in older age, women, and the proximal colon [26].…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Several reports, together with our results, have demonstrated that microsatellite-unstable gastric carcinomas are significantly associated with the elderly [2,[4][5][6], women [3,5], and antral location [2,4,5,9]. These characteristics are similar to those of medullary-type, poorly differentiated adenocarcinoma of the colorectum, which is a representative MSI-positive carcinoma showing predominant occurrence in older age, women, and the proximal colon [26].…”
Section: Discussionsupporting
confidence: 78%
“…The present study demonstrates no significant difference in the proportion of MSI between the differentiated type and the undifferentiated type. Although predominant intestinal-type histology in microsatellite-unstable carcinomas has been widely accepted [2,4,5,9,10,23], several reports have shown predominant poorly differentiated histology [1], or no significant association between histological morphology and MSI [6,[11][12][13]. The differences among these reports were considered to depend upon the specific groups of cases studied and the type and number of markers examined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The frequency of microsatelliteinstable gastric adenocarcinoma in our cohort was 16% vs 21.7% in the Cancer Genome Atlas 6 , 22.7% in the Asian Cancer Research Group, 7 and 8-25.9% in the literature. [40][41][42] The reported incidence is higher in western studies 43 and associated with older age, female gender, larger tumor size, intestinal differentiation, and lower rate of nodal involvement. 40,44 In the Asian Cancer Research Group, the microsatellite-instable subtype was predominantly associated with antral location, early stage, and intestinal phenotype as well.…”
Section: Discussionmentioning
confidence: 99%